Determination of critical power in trained rowers using a three-minute all-out rowing test - Cheng, C.-F.; Yang, Y.-S.; Lin, H.-M.; Lee, C.-L.; Wang, C.-Y. (European Journal of Applied Physiology, 2012)
The purpose of this study was to determine whether the hyperbolic relationship between power output and time to exhaustion (work - time and power - [1/time] models) could be estimated from a modified version of a three-minute all-out rowing test (3-min RT), and to investigate the test-retest reliability of the 3-min RT. Eighteen male rowers volunteered to participate in this study and underwent an incremental exercise test (IRT), three constant-work rate tests to establish the critical power (CP) and the curvature constant (W'), and two 3-min RTs against a fixed resistance to estimate the end-test power (EP) and work-done-above-EP (WEP) on a rowing ergometer. Peak ( [(V)\dot]\textO 2 \textpeak ) \left( {\dot{V}{\text{O}}_{{ 2 {\text{peak}}}} } \right) and maximal ( [(V)\dot]\textO2max ) \left( {\dot{V}{\text{O}}_{2\max } } \right) oxygen uptakes were calculated as the highest 30 s average achieved during the 3-min RT and IRT tests. The results showed that EP and WEP determinations, based on the 3-min RT, have moderate reproducibility (P = 0.002). EP (269 ± 39 W) was significantly correlated with CP (work - time, 272 ± 30 W; power - [1/time], 276 ± 32 W) (P = 0.000), with no significant differences observed between the EP and CP values (P = 0.474). However, WEP did not significantly correlate with W' (P = 0.254), and was significantly higher than the W' values. There was a significant correlation between the [(V)\dot]\textO 2 \textpeak \dot{V}{\text{O}}_{{ 2 {\text{peak}}}} (60 ± 3 ml/kgmin) and [(V)\dot]\textO2max \dot{V}{\text{O}}_{2\max } (61 ± 4 ml kg-1 min-1) (P = 0.003). These results indicate that the 3-min RT has moderate reliability, and is able to appropriately estimate the aerobic capacity in rowers, particularly for the CP and [(V)\dot]\textO2max \dot{V}{\text{O}}_{2\max } parameters.